Conservative Treatment of Severe Pelvic Abscess Post-Cesarean Section in China: A Case Series - Wu X; He X; Lou J (International Journal of Women's Health)
Xiaoli Wu,* Xiaobo He,* Jun Lou Department of Obstetrics, Affiliated Women and Children’s Hospital of Ningbo University, Ningbo, Zhejiang, 315012, People’s Republic of China*These authors contributed equally to this workCorrespondence: Jun Lou, Email mouseloujun@163.comBackground: The rate of cesarean section (CS) is increasing worldwide (especially in China) reaching 51– 65%. Although severe pelvic abscesses after CS are rare, they are difficult to treat. To address this problem, we herein report 23 cases of severe pelvic abscesses and their treatments.Methods: We identified 23 patients with severe pelvic abscesses using International Classification of Disease codes in a retrospective quality assurance analysis.Results: Among 12,640 cesarean deliveries, 23 women (0.182%) developed severe pelvic abscess. Include total numbers for treatments, 69.5% (16/23) treated with debridement, 30.4% (7/23) with antibiotics only. All patients presented with fever lasting 5– 17 days. Imaging (B-ultrasound/MRI) confirmed periuterine abscess cysts in all cases. Pathogens were identified in 18 cases: bacteria (n=14), Mycoplasma suis (n=3), and Rhizopus (fungal, n=1).Conclusion: Our study reported that debridement was a good treatment option, and the patient’s temperatures were controlled after the pus was expelled.Keywords: severe pelvic abscess, cesarean delivery, surgery site infection, case series